TNF-α Induces Phenotypic Modulation in Cerebral Vascular Smooth Muscle Cells: Implications for Cerebral Aneurysm Pathology. Issue 10 (October 2013) - Ali, Muhammad S; Starke, Robert M; Jabbour, Pascal M; Tjoumakaris, Stavropoula I; Gonzalez, L Fernando; Rosenwasser, Robert H; Owens, Gary K; Koch, Walter J; Greig, Nigel H; Dumont, Aaron S
Little is known about vascular smooth muscle cell (SMC) phenotypic modulation in the cerebral circulation or pathogenesis of intracranial aneurysms. Tumor necrosis factor-alpha (TNF-α) has been associated with aneurysms, but potential mechanisms are unclear. Cultured rat cerebral SMCs overexpressing myocardin induced expression of key SMC contractile genes (SM-α-actin, SM-22α, smooth muscle myosin heavy chain), while dominant-negative cells suppressed expression. Tumor necrosis factor-alpha treatment inhibited this contractile phenotype and induced pro-inflammatory/matrix-remodeling genes (monocyte chemoattractant protein-1, matrix metalloproteinase-3, matrix metalloproteinase-9, vascular cell adhesion molecule-1, interleukin-1 beta). Tumor necrosis factor-alpha increased expression of KLF4, a known regulator of SMC differentiation. Kruppel-like transcription factor 4 (KLF4) small interfering RNA abrogated TNF-α activation of inflammatory genes and suppression of contractile genes. These mechanisms were confirmed in vivo after exposure of rat carotid arteries to TNF-α and early on in a model of cerebral aneurysm formation. Treatment with the synthesized TNF-α inhibitor 3, 6-dithiothalidomide reversed pathologic vessel wall alterations after induced hypertension and hemodynamic stress. Chromatin immunoprecipitation assays in vivo and in vitro demonstrated that TNF-α promotes epigenetic changes through KLF4-dependent alterations in promoter regions of myocardin, SMCs, and inflammatory genes. In conclusion, TNF-α induces phenotypic modulation of cerebral SMCs through myocardin and KLF4-regulated pathways. These results demonstrate a novel role for TNF-α in promoting a pro-inflammatory/matrix-remodeling phenotype, which has important implications for the mechanisms behind intracranial aneurysm formation.